EXPLORING NIAS LOCAL WISDOM THROUGH AN ETHNOSCIENCE APPROACH AS A SCIENCE LEARNING RESOURCE IN SCHOOLS - Darmawan Harefa (Universitas Nias Raya, 2026)
This study explores the potential of Nias local wisdom as a science learning resource through an ethnoscience approach in school education. The research aims to identify forms of local knowledge embedded in Nias cultural practices and analyze their relevance to scientific concepts for integration into science learning. A qualitative ethnographic method was employed, involving in-depth interviews, participant observation, and document analysis in selected communities in South Nias, Indonesia. The findings reveal that Nias local wisdom, such as Hombo Batu (stone jumping), traditional house construction (Omo Hada), and indigenous environmental management practices, contains implicit scientific concepts related to physics, biology, and environmental science. These cultural elements can be systematically transformed into contextual science learning resources that enhance students’ understanding and engagement. The ethnoscience approach bridges the gap between students’ cultural background and formal scientific knowledge, making learning more meaningful and relevant. The study also shows that integrating local wisdom into science education supports students’ scientific literacy, critical thinking, and cultural identity. However, challenges such as limited instructional materials and teacher readiness remain in implementing ethnoscience-based learning. Overall, this study concludes that Nias local wisdom has strong potential to enrich science education in schools when appropriately integrated through an ethnoscience framework.